Population Genetic Structure of Three‐Spined Sticklebacks in the St. Lawrence: A Gradient of Change - Sann Delaive; Florent Sylvestre; Amanda Xuereb; Laurie Lecomte; Brian Boyle; Christian Otis; Louis Bernatchez; Nicolas Derome (Ecology and Evolution, 2025)
ABSTRACT Understanding how environmental gradients shape population genetic structure is critical for elucidating evolutionary dynamics in heterogeneous landscapes. The St. Lawrence Estuary, spanning fluvial, middle, and marine zones, presents a steep salinity gradient that serves as an ideal setting to study such a question. Three‐spined sticklebacks (Gasterosteus aculeatus) thrive across these zones, offering an ideal model system to investigate the interplay of gene flow and natural selection in shaping population structure. Using whole‐genome resequencing of sticklebacks from 12 sites, this study aimed to resolve fine‐scale population structure and investigate how genetic diversity and differentiation are influenced by selection and gene flow. By integrating single nucleotide polymorphisms (SNPs) and structural variants (SVs), we assessed differentiation patterns, examined clinal variation, and evaluated the relative roles of gene flow and selection in shaping population dynamics. Our findings reveal clear genetic differentiation between fluvial and saltwater populations, with Baie‐Saint‐Paul forming a potential third group. Salinity emerged as a key driver of genetic structure, with clinal variation in allele frequencies suggesting ongoing adaptation along the gradient. Demographic modeling indicated a history of secondary contact with recent and weak gene flow. Structural variants, particularly indels, complemented SNP‐based analyses, underscoring their importance in detecting fine‐scale population structure. These results highlight the complex interplay of evolutionary forces shaping biodiversity in transitional environments, providing a basis for exploring local adaptation in connected populations and contributing to broader efforts in conservation genomics.